Comparison of Electronic Cow Record (REKS-EL) Feature with Recording Components Used by Dairy Farmers In Sleman Regency, Yogyakarta - Glorina Desviani Desviani; Yuni Suranindyah; Dyah Maharani (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The study was conducted in 60 respondents of dairy farmers in Sleman Regency, Yogyakarta from August 2020 to February 2021. The study aims to make comparison between recording in the REKS-EL version 1.0 and those in dairy farms recording, in order to improve REKS-EL features. Data of the farmer characteristics and recording components were collected by interviewed. Identification of components the dairy farmers recording was carried out using a list of questions in a table. The list contains 43 components, which were arranged based on the recording guidelines as written in the Indonesian Minister of Agriculture No. 100, 2014. The result of comparison between dairy farmers recording and REKS-EL version 1.0 feature showed differences on recording content. Software REKS-EL has more recording components than dairy farmers recording, as much as 23 vs. 13 (46% vs. 23% of total components). The REKS-EL feature showed advantages on data of pedigree, and reproduction but needs to be improved with the additional components derived from farmer records, namely daily and weekly milk production. In the REKS-EL feature also needs to be added feed data, body condition score and calf after birth.